Plant Biomass Allocation-Regulated Nitrogen and Phosphorus Addition Effects on Ecosystem Carbon Fluxes of a Lucerne (Medicago sativa ssp. sativa) Plantation in the Loess Plateau - Penghui Zhai; Rongrong Cheng; Zelin Gong; Jianhui Huang; Xuan Yang; Xiaolin Zhang; Xiang Zhao (Plants)
Nitrogen (N) and phosphorus (P) are key limiting factors for carbon (C) fluxes in artificial grasslands. The impact of their management on ecosystem C fluxes, including net ecosystem productivity (NEP), ecosystem respiration (ER), and gross ecosystem productivity (GEP) in the Loess Plateau is unclear. An experiment was conducted to study changes in these C fluxes with varying N (0, 5, 10, 15, and 20 g N m−2) and P (0 and 10 g P m−2) additions from 2022 to 2023 in a lucerne plantation. Results showed that N addition positively influenced NEP and GEP in the first year after planting with N addition at the rate of 10 g N m−2 was optimal for C assimilation, but it had negligible effect on ER in both two years in the studied lucerne (Medicago sativa ssp. sativa) plantation. Phosphorus addition significantly increased ER and stimulated GEP, resulting in an increasing effect on NEP only at the early stage after planting. The addition of N and P enhanced soil N and P availability and further improved the leaf chemical stoichiometry characteristics, leading to changes in biomass distribution. The more belowground biomass under N addition and more aboveground production under P addition resulted in different responses of ecosystem C fluxes to N and P addition. The results suggest that the effects of N and P fertilization management on the ecosystem C cycle may be largely dependent on the distribution of above- and belowground plant biomass in the artificial grassland ecosystem.